1971
DOI: 10.1002/j.2333-8504.1971.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

College Grading Practices: An Overview1

Abstract: Record and descriptive grading are also used.The most commonly stated purposes of grades are for selection to more advanced educational programs and employment, for motivating students, and for providing students with information about their performance. Consideration of purposes, however, seldom enters decisions about form. Grades are charged with distorting both learning and teaching and undesirably affecting students' attitudes and emotional states, yet evidence either for or against these charges is sparse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Though recent studies find a positive association between undergraduate GPA and graduate school performance (Halberstam & Redstone, 2005;Leavitt et al, 2011;Menifield et al, 2007;Ragothaman, Carpenter, & Davies 2009), past studies highlight the limitations of undergraduate GPA. One of the chief flaws in using undergraduate grade point average is measurement error (Humphreys, 1968;Warren, 1971;Werts, Linn, & Joreskog, 1978). Smith (1992) argues that grade inflation is one possible factor for this incongruity, which thus limits the value of the variable as a predictor of graduate school success.…”
Section: Admission Criteria and Student Successmentioning
confidence: 99%
“…Though recent studies find a positive association between undergraduate GPA and graduate school performance (Halberstam & Redstone, 2005;Leavitt et al, 2011;Menifield et al, 2007;Ragothaman, Carpenter, & Davies 2009), past studies highlight the limitations of undergraduate GPA. One of the chief flaws in using undergraduate grade point average is measurement error (Humphreys, 1968;Warren, 1971;Werts, Linn, & Joreskog, 1978). Smith (1992) argues that grade inflation is one possible factor for this incongruity, which thus limits the value of the variable as a predictor of graduate school success.…”
Section: Admission Criteria and Student Successmentioning
confidence: 99%
“…Findings concluded that students in the latter group demonstrated a higher level of learning, critical thinking skills, and overall course satisfaction (Tynjala, 1998). The already overwhelming evidence against examination-only courses is further supported by studies that found exams to be poor predictors of future success in education or professional careers (Baird, 1985;Warren, 1971) and that coursework is a better indication of long-term learning than exams (Conway, Cohen, & Stanhope, 1992). This information is applicable to MICE education because it demonstrates how assessment directly influences the types of skills students develop throughout the duration of the course.…”
Section: Experiential Exercisementioning
confidence: 96%
“…According to Conway (1992), efforts that students used in completing formative assessment bring a long term impacts in learning compared to revising for an examination. Warren (1971) points out that summative assessment is a weak predictor of long term learning and following performance compared to formative assessment.…”
Section: Formative Assessment Vs Summative Assessmentmentioning
confidence: 99%